2008
DOI: 10.1103/physrevb.78.235433
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the stable states of small carbon clustersCn(n=210)

Abstract: Both even-and odd-numbered neutral carbon clusters C n (n = 2-10) are systematically studied using the energy minimization method and the modified Brenner potential for the carboncarbon interactions. Many stable configurations were found and several new isomers are predicted. For the lowest energy stable configurations we obtained their binding energies and bond lengths. We found that for n ≤ 5 the linear isomer is the most stable one while for n > 5 the monocyclic isomer becomes the most stable. The latter wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 36 publications
5
30
1
1
Order By: Relevance
“…As shown in Ref. [28] all the C-C bonds in the chain are not identical and therefore all the spring constants between the C-atoms are expected not to be identical, which is the reason why our simple model does not give perfect agreement with our numerical data.…”
Section: Linear and Ring Clusterscontrasting
confidence: 47%
See 1 more Smart Citation
“…As shown in Ref. [28] all the C-C bonds in the chain are not identical and therefore all the spring constants between the C-atoms are expected not to be identical, which is the reason why our simple model does not give perfect agreement with our numerical data.…”
Section: Linear and Ring Clusterscontrasting
confidence: 47%
“…The lowest energy, i.e. the ground state [27,28] configurations were determined for up to N=55 carbon atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we found that the structure of Si clusters inside bilayer graphene is totally different from free standing Si clusters (see, e.g., Ref. 42 ) and for N >5 resembles (but are not identical) the ones observed for carbon clusters in vacuum 41 .…”
Section: Structural Propertiesmentioning
confidence: 59%
“…where N is the number of Si atoms in the cluster, δ i is the Lindemann index of atom i and δ is the Lindemann index for the entire cluster 41 . Figure 5 shows the Lindemann index of Si 6 (circles), Si 16 (squares) and Si 24 (triangles) clusters as a function of temperature.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…The ionization potentials of 96 Zr and 12 C 8 cluster were not included in the calculation as they differ only by a few eV. However the molecular binding energy of the 12 C 8 cluster, which, in its most stable ringlike geometry, is -45.18 eV [21], is significant at our uncertainty level and was thus included in Eqn. 3.…”
Section: Q Value Determination Of 96 Zrmentioning
confidence: 99%